International conflict resolution - Hauss, Charles (New York : Continuum, 2010)
Using a broad range of case studies, this book examines conflict and the international relations facing the world today. The book looks at conflict both as an important subject in its own right and as a powerful lens through which to view international relations more generally.
pt. 1. Introduction -- Ch. 1. Passion, Argument, Evidence, Insight -- Ch. 2. Understanding Conflict -- pt. 2. Theory -- Ch. 3. The Role of Theory -- Ch. 4. International Relations Theory and Conflict Resolution -- pt. 3. Case Studies -- Ch. 5. South Africa -- Ch. 6. Northern Ireland -- Ch. 7. Israel and the Palestinians -- Ch. 8. The Global War on Terrorism -- Ch. 9. Iraq -- Ch. 10. Darfur -- pt. 4. Conclusions -- Ch. 11. Intellectual Conclusions -- Ch. 12. Political Conclusions.
Includes bibliographical references and index.
Keywords: Pacific settlement of international disputes; International relations; Conflict management